The Accuracy of Ankle Eccentric Torque Control Explains Dynamic Postural Control During the Y-Balance Test - Shojiro Nozu; Kristin A. Johnson; Tsukasa Tanaka; Mika Inoue; Hirofumi Nishio; Yuji Takazawa (International Journal of Sports Physical Therapy)
# Background